Linking carbonate sediment transfer to seafloor morphology: Insights from Exuma Valley, the Bahamas. Issue 2 (8th October 2020) - Le Goff, Johan; Recouvreur, Audrey; Reijmer, John J.G.; Mulder, Thierry; Ducassou, Emmanuelle; Perellò, Marie‐Claire; Hanquiez, Vincent; Gillet, Hervé; Cavailhes, Thibault; Fabregas, Natacha
Abstract: The depositional record of carbonate slopes provides a valuable archive of past environmental and climatic changes. Modern carbonate slopes reveal morphological variabilities (for example, gullies and canyons) shaped by episodic slope collapses and turbidity currents. Furthermore, climate‐induced fluctuations in sea level regulate sediment availability and delivery to the deep‐sea. Morphological and climatic controls on calciclastic sediment transfer are often complex to decipher. The aim of this study is to link seafloor morphology and depositional processes in an active carbonate submarine channel (Exuma Valley, the Bahamas) over the last 40 kyr. The dataset includes multibeam and seismic surveys, and two sediment cores retrieved from the valley axis. A series of abrupt slope‐breaks, called knickpoints, occurs along Exuma Valley, and plays a key role in sediment transport and accumulation. Initiation processes proposed for knickpoint formation include bank‐collapse, side gully erosion and loss of confinement. Slope collapses detected on the bathymetry prevail in the upstream muddy section of the submarine valley, as attested to by a planktic‐rich debrite–turbidite couplet in the first core. In contrast, the second core collected downstream of the knickpoints train, includes 32 bioclastic sandy event‐beds (i.e. turbidites). Hydrodynamic sorting generates grain segregation (for example, Halimeda ‐rich base versus planktic‐rich top) and geochemical contrasts (Sr/Ca) in turbidites. Turbidite frequency and grain composition within beds reflect the variation of carbonate sources during glacial–interglacial periods. This research allows to link slope morphology with deposits of a modern large‐scale carbonate factory, and to deduce sea‐level changes over that last 40 kyr in the Bahamas. These results can provide new perspectives on the understanding of 'source to sink' mechanisms in carbonate systems.